Penerapan Metode Diskusi Dan Tanya Jawab Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Pada Siswa Kelas V SD Negeri 148 Palembang - Nurlina Nurlina (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The problem in this research is "Low results of learning Indonesian for class V at SDN 148 Palembang." The aim of this research is to improve learning outcomes for Indonesian by using discussion and question and answer methods in class V at SDN 148 Palembang. This research was carried out at SDN 148 Palembang. The research subjects were 25 class V students. The instruments used to collect data in this research used tests and observations. Student learning outcomes in cycle I when the discussion and question and answer method was applied was an average of 66.8 with a percentage of student learning completeness of 75% from 25 students after the teacher reflected and corrected several deficiencies so that student learning outcomes in cycle II increased, namely, grades. an average of 78.8 with a percentage of student learning completeness of 85%. Out of 25 students, the number of students has reached the standard of learning completeness. It was concluded that the application of the discussion and question and answer method in Indonesian language subjects in class V at SDN 148 Palembang could improve student learning outcomes. This means that the application of discussion and question and answer methods can be used as an alternative in learning Indonesian.